Mechanically strong porous bioceramic tubes facilitate large segmental bone defect repair by providing long-term structurally stability and promoting osteogenesis - Lijun Xie; Jiahao Zhang; Hangxiang Sun; Zehao Chen; Wangsiyuan Teng; Xupeng Chai; Cong Wang; Xianyan Yang; Yifan Li; Sanzhong Xu; Zhongru Gou; Zhaoming Ye (Engineered Regeneration, 2024)
Mechanically strong magnesium-doped Ca-silicate bioceramic scaffolds have many advantages in repairing large segmental bone defects. Herein we combine β-TCP with 6 mol% magnesium-doped calcium silicate (Mg6) at three different ratios (TCP, TCP+15 %Mg6, TCP+85 %Mg6) to find an appropriate ratio which can exert considerable influence on bone regeneration. In this study, the bioceramic scaffolds were assessed for mechanical strength, bioactive ion release, biocompatibility, and osteogenic capacity through in vitro testing. Additionally, the potential for promoting bone regeneration was investigated through in vivo implantation of porous tube-like scaffolds. The results showed that the compressive strength increased with the augmentation of Mg6 component. Especially the compressive strength of the TCP+85 %Mg6 group reached 38.1 ± 3.8 MPa, three times that of the other two groups. Furthermore, extensive in vivo investigations revealed that the TCP+85 %Mg6 bioceramic scaffolds were particularly beneficial for the osteogenic capacity of critical-sized femoral defects (20 mm in length). Altogether, magnesium doping in bioceramic implants is a promising strategy to provide stronger mechanical support and enhance osteogenesis to accelerate the repair of large defects.